Interactions between glucocorticoid metabolism and inflammation in obesity and insulin resistance. - Nixon, Mark (The University of Edinburgh, 2011)
Inflammation plays a key role in the underlying pathogenesis of obesity and its associated health risks, with increased markers of inflammation evident in both liver and adipose tissue. In parallel, there is dysregulation of glucocorticoid metabolism in obesity, with increased adipose levels of the glucocorticoid-regenerating enzyme 11β-hydroxysteroid dehydrogenase type 1 (11βHSD1) and increased hepatic levels of 5α-reductase type 1 (5αR1), which catalyses the reduction of glucocorticoids. Both the mechanisms and consequences of this glucocorticoid metabolism dysregulation remain unclear, however, there is evidence that it may be related to inflammation. In vitro studies have demonstrated that pro-inflammatory markers upregulate 11βHSD1 expression in adipocytes, potentially explaining increased expression of this enzyme in obesity. Previous work has also demonstrated that the glucocorticoid metabolites produced by 5αR1 lack the metabolic effects of the parent glucocorticoid, but retain its anti-inflammatory properties, indicating that increased expression of hepatic 5αR1 may serve to dampen down inflammation in the liver. The hypotheses addressed in this thesis are that in obesity, inflammation regulates adipose glucocorticoid metabolism through 11βHSD1, and that hepatic glucocorticoid metabolism regulates the inflammatory state of the liver through 5αR1. The role of inflammation in the regulation of 11βHSD1 was assessed in vivo in mice treated with the anti-inflammatory compound sodium salicylate (salicylate). In diet-induced obese mice, salicylate downregulated 11βHSD1 expression and activity selectively in visceral adipose tissue, alongside improved glucose tolerance, reduced plasma non-esterified fatty acids, and changes in adipose lipid metabolism. 11βHSD1-deficient mice fed a high-fat diet were resistant to the insulin sensitising effects of salicylate treatment. These results indicate a novel role for 11βHSD1 down-regulation in mediating the insulin sensitising effect of anti-inflammatory treatment. The mechanisms underpinning the anti-inflammatory properties of 5α-reduced glucocorticoids were explored in vitro and in vivo. In lipopolysaccharide-stimulated murine macrophages, both 5α-reduced glucocorticoid metabolites tested, namely 5α-dihydrocorticosterone (5αDHB) and 5α-tetrahydrocorticosterone (5αTHB), suppressed tumor necrosis factor-α (TNFα) and interleukin-6 (IL-6) release, although to a lesser extent than corticosterone (B). Similar to B, both 5αDHB and 5α THB suppressed phosphorylation of intra-cellular inflammatory signalling mitogen-activated protein kinases (MAPK) proteins c-Jun N-terminal kinase (JNK) and p38, as well as increasing protein expression of MAPK phosphatase-1 (MKP-1). Treatment of phorbol ester-stimulated HEK293 kidney cells with these 5α-metabolites revealed that 5αDHB suppressed nuclear factor κB (NFκB) and activator protein-1 (AP-1) activation to a similar extent to that of B, whilst 5αTHB increased activation of these pro-inflammatory transcription factors, indicating cell-specific effects of 5αTHB. In conclusion, reduced intra-adipose glucocorticoid regeneration by 11βHSD1 mediates the insulin sensitising effects of salicylate, suggesting that altered glucocorticoid metabolism may reflect altered intra-adipose inflammation in obesity. Furthermore, these data support the concept that this enzyme provides a therapeutic target in obesity-related metabolic disorders. 5α-reduced metabolites of glucocorticoids have similar anti-inflammatory properties to the parent glucocorticoid, indicating that the elevated hepatic levels of 5α-reductase in obesity may be a protective mechanism to limit the adverse metabolic effects of glucocorticoids upon the liver, but maintain the beneficial anti-inflammatory properties. These 5α-reduced glucocorticoid metabolites may provide a potential therapeutic treatment as selective glucocorticoid receptor modulators for inflammatory conditions.
Keywords: inflammation; adipose tissue; 11 Beta Hydroxysteroid Dehydrogenase type 1; 11β-HSD1; glucocorticoids; 5αR1; anti-inflammatory